Project management success I-C-E model: a work in progress - Marques, António (2013)
Project management in software development has shown high rates of failure since the beginning of computation. Over the last years, several studies have sought and proposed solutions for this problem by focusing, for instance, on success critical aspects and evaluation criteria. Although these efforts have provided a significant evolution in how the work is done, project management success rates are in fact still well below the desirable values. This paper presents a work-inprogress based on an integrated approach to project management success and proposes a model that considers jointly the set of success influencers, project characteristics and evaluation criteria of success, from the initiation of a project until its closure.